LEGAL BASIS FOR RECORDING OF DESTROYED (DAMAGED) PROPERTY OF THE CIVILIAN POPULATION DURING ARMED CONFLICTS - Tarnopolova, M. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The issue of recording, recording and summarizing information about the destroyed (damaged) property of the civilian population during armed conflicts is important not only in view of the protection of the rights and security of the population, the interests of the state, but also a significant tool for proving the compliance of the security and Defense Forces of Ukraine with the norms of international humanitarian law (the law of armed conflicts) in the context of prohibiting or restricting the use of certain means and methods of conducting armed struggle, ensuring the protection of victims of conflict and bringing the aggressor state to justice for violating these norms. It is the provision of reliable and objective information containing a list of exhaustive evidence regarding the destruction (damage) of civilian property during armed conflicts that can become in the future ongoing armed conflict a basis for: positioning Ukraine as a conscious state governed by the rule of law; compliance by the Armed Forces of Ukraine with the obligation not to cause harm to persons and objects that are protected by international humanitarian law (including civilian objects); increasing the level of trust on the part of the population of our state, both to the security and Defense Forces of Ukraine, and the state authorities as a whole. The article discusses the legal basis and relevance of determining the system and mechanisms for recording and recording destroyed (damaged) property of the civilian population during armed conflicts by both representatives of the Armed Forces of Ukraine and representatives of state authorities. It is stated that compensation for the cost or restoration of destroyed (damaged) objects should be preceded by high-quality recording and accounting, which is why it is appropriate to introduce a method developed by the Armed Forces of Ukraine to track damage to the civilian population in all areas where active military operations are conducted (were conducted) in order to collect evidence and facts of human rights violations during a full-scale war of the Russian Federation against Ukraine in relation to the destroyed (damaged) property of the civilian population.